2019
DOI: 10.1111/tmi.13326
|View full text |Cite
|
Sign up to set email alerts
|

Can a family medicine rotation improve medical students’ knowledge, skills and attitude towards primary care in Vietnam? A pre‐test–post‐test comparison and qualitative survey

Abstract: objectives Well-designed studies on the impact of a family medicine rotation on medical students are rare, and very few studies include a qualitative component. This study aimed to determine the improvement of medical students' knowledge, communication skills and attitude towards primary care and explore their perceptions after rotations, in comparison with a control group.methods We used a mixed-methods design, comprising a pre-test-post-test comparison between a sample of trained students who took family med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Pre‐clerkship placements mitigate this stigma by demonstrating the positive aspects of generalist specialties, and exposing students to FM role models and mentors that better promote generalist careers 45,56 . Indeed, this was the finding in a study conducted in Vietnam where attitudes regarding FM were shown to be more positive in the group that participated in a 2‐week FM rotation compared to its control 57 . Regardless of eventual specialty interest, early placements may help improve attitudes and perspectives of FM in medical school 33,58‐64 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pre‐clerkship placements mitigate this stigma by demonstrating the positive aspects of generalist specialties, and exposing students to FM role models and mentors that better promote generalist careers 45,56 . Indeed, this was the finding in a study conducted in Vietnam where attitudes regarding FM were shown to be more positive in the group that participated in a 2‐week FM rotation compared to its control 57 . Regardless of eventual specialty interest, early placements may help improve attitudes and perspectives of FM in medical school 33,58‐64 …”
Section: Discussionmentioning
confidence: 95%
“…shown to be more positive in the group that participated in a 2-week FM rotation compared to its control. 57 Regardless of eventual specialty interest, early placements may help improve attitudes and perspectives of FM in medical school.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the family medicine rotation had an impact on students' knowledge, attitude and skills towards family medicine. 8 However, the lower status of family medicine in comparison to other specialties may lead to low levels of interest in this discipline by students and medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…In LMICs which incorporate PHC competencies into UME, students value their experiences at PHC sites [ 9 16 17 18 19 ]. In countries with newly developing PHC curricula, a first step is introducing an elective in a PHC setting [ 20 21 22 ]. Beyond these elective experiences, there are few examples of UME curricula required for all students.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, medical educators across Viet Nam collaborated to promote a community-centred approach to UME through the identification of learning objectives and outcomes expected of medical graduates [ 26 27 28 29 ]. In places where family medicine existed, universities created family medicine rotations [ 22 ]. The implementation of community-centred learning objectives predominately manifests as short periods where students participate in public health campaigns such as childhood immunization programmes and tuberculosis control [ 30 ].…”
Section: Introductionmentioning
confidence: 99%